2019
DOI: 10.12659/msm.914269
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Strontium-Loaded, Phase-Transited Lysozyme Coating to a Titanium Surface to Enhance Osteogenesis and Osteoimmunomodulation

Abstract: Background To fabricate strontium (Sr)-incorporated titanium (Ti) surfaces by a novel 1-step phase-transited lysozyme (PTL) treatment, and investigate the effects of the prepared samples on osteogenesis and osteoimmunoregulation. Material/Methods Five groups of titanium specimens were prepared, including Ti, PTL, PTL@10Sr (PTL coating with 10 mg/mL Sr), PTL@20Sr PTL coating with 20 mg/mL Sr), and PTL@50Sr (PTL coating with 50 mg/mL Sr) groups. Behaviors of bone marrow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 64 publications
1
9
0
1
Order By: Relevance
“…On the other hand, NF-κB activity tended to decrease in the latter phase of fracture healing in both the non-scaffolded as well as the β-TCP-scaffolded group, but in the strontium (+ Sr) group, by contrast, NF-κB activity shows a significant increase beginning around day 40 after the fracture. The immunomodulatory properties of Sr is discussed in some studies [25,33], but as far as we know, such an anti-inflammatory effect of strontium has never been reported in a study featuring longitudinal monitoring. Acute inflammation is a crucial biological process for tissue homeostasis in the early phase of fracture healing.…”
Section: Longitudinal Nf-κb Activity During Fracture Healingmentioning
confidence: 99%
“…On the other hand, NF-κB activity tended to decrease in the latter phase of fracture healing in both the non-scaffolded as well as the β-TCP-scaffolded group, but in the strontium (+ Sr) group, by contrast, NF-κB activity shows a significant increase beginning around day 40 after the fracture. The immunomodulatory properties of Sr is discussed in some studies [25,33], but as far as we know, such an anti-inflammatory effect of strontium has never been reported in a study featuring longitudinal monitoring. Acute inflammation is a crucial biological process for tissue homeostasis in the early phase of fracture healing.…”
Section: Longitudinal Nf-κb Activity During Fracture Healingmentioning
confidence: 99%
“…According to the peeling test, the weight loss of the pure PPy substrate and PPy/PTLP composite are 17.53% and 3.80% comparing to the original mass respectively, indicating that the adhesion of PPy/PTLP composite is higher due to the bio‐adhesive of lysozyme 45 . The lysozyme deposition is rich in amyloid assembly structure, which may have hydrophobic interaction force, hydrogen bonding, and electrostatic effect with unique bio‐adhesion property 42–44 …”
Section: Resultsmentioning
confidence: 99%
“…It is reported that lysozyme can be transmitted to assembled nanoparticles with self‐adhesion on various substrates via a phase transition process 42 . This assembly may act as a template and induce the aggregation of organic/inorganic materials to generate homogenous hybrids 2,42–44 . During the assembled process, the lysozyme nanoparticles may deposit on different substrates in aqueous environmental 42,45–49 .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 9 ] and Wang et al [ 37 ] found that the strontium phosphate (including strontium apatite, strontium hydrogen phosphate) coatings on the surface of a magnesium (Mg) alloy can promote proliferation and differentiation of human mesenchymal stem cells and MC3T3E1 cells in vitro, as well as induce further bone formation in vivo. It has also been reported that the Sr-loaded phase-transited lysozyme (PTL) coating invokes greater osteogenesis ability by its effects on the immune environment due to the constant release of Sr ions directly at the implant-tissue interface [ 38 ]. Su et al [ 39 ] discovered that the Zn ion that exist in the form of zinc phosphate, plays a key role in improving osseointegration and immune regulation.…”
Section: Discussionmentioning
confidence: 99%